MAKNA RITUAL SESAJEN DALAM AJAR PIKUKUH SUNDA (SUNDA WIWITAN) (Sudi Terhadap Penganut Ajar Pikukuh Sunda Di Padepokan Bumi Dega Sunda Academy Bandung) - Miharja, Deni; Wahida, Endah; Huriani, Yeni (UIN Sunan Kalijaga Yogyakarta, 2021)
Indonesia is a country that has many local cultures including one of them is Ajar pikukuh sunda (Sundanese Wiwitan) which is in Padepokan Bumi Dega Sunda Academy Bandung. In the teachings of Sundanese pikukuh there is a ritual that is always carried out, namely the offering. However, many people misinterpret the ritual offerings so that they are referred to as givers of demons and polytheists. The purpose of this study was to determine the meaning of offerings in Sundanese Pikukuh (Sunda Wiwitan) Teachings at Padepokan Bumi Dega Sunda Academy Bandung. This research methodology is descriptive qualitative with case studies. The results of this paper conclude that the ritual offerings carried out in Ajar Pikukuh Sunda (Sundanese Wiwitan) have a very high and noble meaning. The teaching materials / means in the ritual are all the same, namely water, earth, fire, and wind, animal elements, and plant elements. The meaning of offerings carried out by the Sundanese Pikukuh Teachers at Padepokan Bumi Dega Sunda Academy Bandung is a prayer ritual as a form of gratitude to our ancestors, the universe, to our parents, or to everything that has supported us so far, because without them we will never exist so that by using the means of sasajen from the natural elements it will be able to reconnect the energy of the past with the future.Keywords : Mean; Sesajen; Ajar Pikukuh Sunda (Sunda Wiwitan);Indonesia is a country that has many local cultures including one of them is Ajar pikukuh sunda (Sundanese Wiwitan) which is in Padepokan Bumi Dega Sunda Academy Bandung. In the teachings of Sundanese pikukuh there is a ritual that is always carried out, namely the offering. However, many people misinterpret the ritual offerings so that they are referred to as givers of demons and polytheists. The purpose of this study was to determine the meaning of offerings in Sundanese Pikukuh (Sunda Wiwitan) Teachings at Padepokan Bumi Dega Sunda Academy Bandung. This research methodology is descriptive qualitative with case studies. The results of this paper conclude that the ritual offerings carried out in Ajar Pikukuh Sunda (Sundanese Wiwitan) have a very high and noble meaning. The teaching materials / means in the ritual are all the same, namely water, earth, fire, and wind, animal elements, and plant elements. The meaning of offerings carried out by the Sundanese Pikukuh Teachers at Padepokan Bumi Dega Sunda Academy Bandung is a prayer ritual as a form of gratitude to our ancestors, the universe, to our parents, or to everything that has supported us so far, because without them we will never exist so that by using the means of sasajen from the natural elements it will be able to reconnect the energy of the past with the future.